Critical Role of Organic Spacers for Bright 2D Layered Perovskites Light‐Emitting Diodes. Issue 7 (19th February 2020) - Tsai, Hsinhan; Liu, Cunming; Kinigstein, Eli; Li, Mingxing; Tretiak, Sergei; Cotlet, Mircea; Ma, Xuedan; Zhang, Xiaoyi; Nie, Wanyi
Abstract: Light‐emitting diodes (LEDs) made with quasi‐2D/3D and layered perovskites have undergone an unprecedented surge as their external quantum efficiency (EQE) is rapidly approaching other lighting technologies. Manipulating the charge recombination pathway in semiconductors is highly desirable for improving the device performance. This study reports high‐performance layered perovskites LEDs with benzyl ring as spacer where radiative recombination lifetime is longer, compared with much shorter alkyl chain spacer yields. Based on detailed optical and X‐ray absorption spectroscopy measurements, direct signature of charges localization is observed near the band edge in exchange with the shallow traps in benzyl organics containing layered perovskites. As a result, it boosts the photoluminescence intensity by 7.4 times compared to that made with the alkyl organics. As a demonstration, a bright LED made with the benzyl organics with current efficiency of 23.46 ± 1.52 cd A −1 is shown when the device emits at a high brightness of 6.6 ± 0.93 × 104 cd m −2 . The average EQE is 9.2% ± 1.43%, two orders of magnitude higher than the device made with alkyl organics. The study suggests that the choices of organic spacers provide a path toward the manipulation of charge recombination, essential for efficient optoelectronic device fabrications. Abstract : The charge recombination pathways in layered perovskites are closely related to the choice of the organic spacers. Using phenylethylamine as organic spacer greatly extends the charge recombination lifetime by localizing the hole near the band edge. Efficient Ruddlesden–Popper layered perovskites light emitting‐diodes are thus demonstrated.